Novel Therapies Based on Cationic Antimicrobial Peptides - Anne Pereira, H. (Current Pharmaceutical Biotechnology, 2006)
Cationic antimicrobial peptides serve as critical defense molecules protecting the host from invading bacteria, viruses and fungi. These antimicrobial peptides are widely distributed in nature and in vertebrates they have been localized to numerous tissues and cells. Cationic antimicrobial peptides can be expressed constitutively or under certain circumstances they can be induced in response to infection, inflammatory mediators, and cytokines. Although, their original and primary function was believed to be antimicrobial, it is now becoming clear that these antimicrobial peptides have a wide repertoire of functions with interesting ramifications on the immune system that are not solely antimicrobial. An area of active research is the determination of the mechanism(s) of action of antimicrobial peptides which have yet to be clarified. However, current consensus is that the mechanism is sufficiently different from conventional antibiotics that the development of resistance could be remote. Their broad spectrum activity, low potential to induce resistance and diverse functions make antimicrobial peptides an attractive family of compounds that have potential to be developed as therapeutics for treating certain infections.
Keywords: endothelium